2019
DOI: 10.16965/ijar.2019.237
|View full text |Cite
|
Sign up to set email alerts
|

Variations on Arterial Supply of Thyroid Gland and Its Clinical Significance in Selected Universities of North Ethiopia

Abstract: Thyroid gland is the largest endocrine gland supplied by the superior, inferior thyroid arteries and occasionally by thyroid ima artery. Proper identification of thyroid gland vessels is very important in order to avoid major complications during and after neck surgeries. The objective of this study was to assess variations on arterial supply of thyroid gland and its clinical significance in human cadavers in selected universities of north Ethiopia.A descriptive survey study design was employed to assess the v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Tsegay et al [ 12 ] performed a cadaveric study in 2019 and observed that, the ECA was identified as the most frequent location of STA origin. The TCT gave rise to the ITA in each case, while in the present study the result for STA corresponds with the given study as in majority of cases the STA arises from ECA on both the sides, whereas in the case of ITA present study does not correspond with given study as in present study the ITA takes origin from thyrocervical trunk, SA, and VA in 201 (95.7%), 7 (3.3%) and 2 (1.0%) cases, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Tsegay et al [ 12 ] performed a cadaveric study in 2019 and observed that, the ECA was identified as the most frequent location of STA origin. The TCT gave rise to the ITA in each case, while in the present study the result for STA corresponds with the given study as in majority of cases the STA arises from ECA on both the sides, whereas in the case of ITA present study does not correspond with given study as in present study the ITA takes origin from thyrocervical trunk, SA, and VA in 201 (95.7%), 7 (3.3%) and 2 (1.0%) cases, respectively.…”
Section: Discussionmentioning
confidence: 99%